2021
DOI: 10.2174/1871527320666210506185042
|View full text |Cite
|
Sign up to set email alerts
|

Carvacrol as a Potential Neuroprotective Agent for Neurological Diseases: A Systematic Review Article

Abstract: Background & objective: Neurological diseases are becoming a significant problem worldwide, with the elderly at a higher risk of being affected. Several researchers have investigated the neuroprotective effects of Carvacrol (CAR) (5-isopropyl-2-methyl phenol). This review systematically surveys the existing literature on the impact of CAR when used as a neuroprotective agent in neurological diseases. Methods: The systematic review involved English articles published in the last ten years obtained from Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…However, carvacrol attenuated Aβ1-42-induced neurotoxicity. These findings are in line with the neuroprotective effects of carvacrol demonstrated in previous studies (Dati et al, 2017;Jukic et al, 2007;Shahrokhi Raeini et al, 2020;Zamanian et al, 2021). Moreover, carvacrol attenuated these Aβ1-42-induced increases in levels of MDA and H 2 O 2 in both cell culture and hippocampal tissue in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, carvacrol attenuated Aβ1-42-induced neurotoxicity. These findings are in line with the neuroprotective effects of carvacrol demonstrated in previous studies (Dati et al, 2017;Jukic et al, 2007;Shahrokhi Raeini et al, 2020;Zamanian et al, 2021). Moreover, carvacrol attenuated these Aβ1-42-induced increases in levels of MDA and H 2 O 2 in both cell culture and hippocampal tissue in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to oxidative stress, neuroinflammation is also implicated in the pathogenesis of AD (Calsolaro & Edison, 2016). No inflammatory markers were measured in the present study, although carvacrol may also have ameliorated the impairments in the in vitro and in vivo models of AD through its anti-inflammatory effect, since carvacrol has been demonstrated to exhibit anti-inflammatory effects in some neurological disorders (Mrak, 2009;Schwab & McGeer, 2008;Silva et al, 2018;Zamanian et al, 2021). For instance, it has recently been shown that carvacrol improved memory impairments by suppressing inflammatory mediators in lipopolysaccharide-induced memory impairment in rats (Lee et al, 2020).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Carvacrol, a monoterpenoid phenol in many aromatic plants, including thyme and oregano, is used as a food flavouring, additive, fragrance, and preservative [ 16 ]. Carvacrol also has a range of biological actions, including anti-cancer, neuroprotective, immunopromoting, antibacterial, antifungal, antiviral, and insecticide effects [ 17 , 18 , 19 , 20 , 21 , 22 ]. Carvacrol shows antimicrobial activity against major plant pathogens, such as Fusarium oxysporum [ 15 ], Cladosporium herbarum [ 23 ], and Penicillium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic brain injury (TBI) is responsible for numerous deaths and permanent disability associated with the advancement of secondary brain injury and bleeding, due to which there is an increase in the rate of morbidity and mortality [1]. Every year, around 3.17 million cases of deaths and disabilities related to TBI are experienced [2].…”
Section: Introductionmentioning
confidence: 99%